Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas Tenaga Kerja Kota Samarinda - Nurhayati, Nabila Armuna; Hadiyanti, Sofia Ulfa Eka; Anitra, Vera (International Journal Administration, Business & Organization, 2025)
The success of public organizations, such as the Samarinda City Manpower Office, is greatly influenced by the performance of its employees. Work discipline is one of the key factors contributing to productivity and operational efficiency. This study aims to analyze the relationship between work discipline and employee performance using a quantitative approach. The population in this study consisted of 70 people, and the sample used was 60 people, selected randomly based on a predetermined sampling formula. Data was collected through the distribution of questionnaires to respondents. Data analysis was performed using simple linear regression. The results of the study showed a strong and significant correlation between the level of work discipline and employee performance. These findings suggest that improving work discipline has a positive impact on productivity. Practically, these results emphasize the importance of implementing consistent discipline policies and work discipline training programs as part of an organizational performance improvement strategy. This study reinforces organizational behavior theory, which states that internal factors such as work discipline contribute significantly to performance. The uniqueness of this study lies in its specific focus on work discipline as a dominant variable in the local context of Samarinda, as well as its use of a quantitative approach that provides an empirical basis for data-driven decision-making in public sector human resource management.